Fundamentos éticos da educação: uma análise a partir do movimento escola sem partido - Ferreira, Verônica Ventorini (Universidade do Vale do Rio dos Sinos, 2019)
This masters dissertation talks about teaching ethics, also proposes to understand the ethical basement of Movimento Escola Sem Partido, also known as No Indoctrination. This study is divided in two sections, the first one with a hermeneutic perspective, whereby the concepts and speeches are analyzed as of historical and political horizons. The following section has a critical tone, therefore, duo to what was explained in the first part, its proposal is to deal with the directing teaching ethics, beginning from the scientific knowledge and the recognition of the other in his otherness.The research is oriented by historical-critical theory, as of the viewpoint of Dermeval Saviani, and by the Hermeneutic-Philosophical, marked by Hans-Georg Gadamer. The methodology applied was documentary research, means that the “word” document indicates all forms the past and the tradition show up, and some articles and sections were taken from the Movimento Escola Sem Partido website. From analyzing articles published by professors in the academy, it was possible to see that the reading of the critical tradition, as well as of the Weberian thought, is made without methodological rigor. Such lack of rigor disqualifies the discourse analyzed, removing the authority of academic titles, to support opinion discourses, distorting the relationship of collaboration between universities and basic education, in so far as it makes the diagnostic of a probable field deficiency, the assumption to uphold coercion on teachers, rather than creating a debate to qualify the education field. Our conclusions point to the urgency of rethinking the teachers' ethics area, based on the educational fundamentals and the intrinsic relation between education, human formation and economic, social and political conditioning factors. That is, the impossibility of thinking about education without understanding it as a field that traverses existence. On the other hand, we contributed to the epistemological debate of the field, based on the considerations of Gadamer and Saviani.
Keywords: Educação; Formação; Políticas educacionais; Filosofia da Educação; Escola sem Partido; Education; Formation; Public Policy; Education Philosophy; Escola sem Partido; ACCNPQ::Ciências Humanas::Educação